STUDENTS’ MISCONCEPTIONS IN INTERPRETING THE MEAN OF THE DATA PRESENTED IN A BAR GRAPH - Rahmatina, Desi; Zaid, Norasykin Mohd (Universitas Negeri Malang, 2019)
Interpreting the mean of the data presented in a bar graph constitutes a mix of two concepts highly useful for testing students? level of understanding of the mean. This study aimed to describe students? misconceptions in the interpretation of the mean of data that are represented in a bar graph and the causes of such misconceptions and to examine whether misconceptions differed by gender and grade. The participants of this study consisted of 112 students (48 males, 64 females) of the Natural Science program of SMAN 1 Tanjungpinang in three grades?tenth, eleventh, twelfth. Employing a mixed method with an exploratory sequential design, this study collected and analyzed qualitative data prior to quantitative ones. The research identified 12 misconceptions about the mean and 8 causes of such misconceptions, and based on the chi-squared test results, neither gender- nor grade-based difference in students? misconceptions was found. These results have an implication for teachers and other educational stakeholders in considering the achievement of learning objectives and core competences in the learning process, especially in the processing, reasoning, and presentation of the mean of data that are presented in a bar graph.